2009
DOI: 10.1007/s00787-008-0725-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of atomoxetine as add-on to psychoeducation in the treatment of attention deficit/hyperactivity disorder

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 32 publications
9
71
1
Order By: Relevance
“…In the 12-week study (n=151), the effect size at 6 weeks (0.55) increased in a linear direction to 0.82 at 12 weeks with no suggestion of a plateau, while maximal placebo response was reached at 6 weeks (Montoya et al, 2009). Similar results were seen using change in ADHD-RS in the 10-week study, giving a final effect size of 1.3, with 63% of patients having a response of >40% (Svanborg et al, 2009), although this study was not powered to measure the effect size using ADHD-RS. In the 6-week study there appeared to be a linear reduction with no suggestion of plateau at 6 weeks (Martényi et al, 2010).…”
Section: Time To Full Response Randomised Double-blind Studies Threesupporting
confidence: 59%
See 3 more Smart Citations
“…In the 12-week study (n=151), the effect size at 6 weeks (0.55) increased in a linear direction to 0.82 at 12 weeks with no suggestion of a plateau, while maximal placebo response was reached at 6 weeks (Montoya et al, 2009). Similar results were seen using change in ADHD-RS in the 10-week study, giving a final effect size of 1.3, with 63% of patients having a response of >40% (Svanborg et al, 2009), although this study was not powered to measure the effect size using ADHD-RS. In the 6-week study there appeared to be a linear reduction with no suggestion of plateau at 6 weeks (Martényi et al, 2010).…”
Section: Time To Full Response Randomised Double-blind Studies Threesupporting
confidence: 59%
“…The 10-12 week treatment-naïve studies also found larger effect sizes for ATX (0.8-1.3) than generally accepted, and emphasise the clinical value of using treatment-naïve populations as a baseline comparator in ADHD (Montoya et al, 2009;Svanborg et al, 2009). In the Newcorn 2008 comparative 6-week study, although efficacy was significantly greater in the OROS-MPH cohort than ATX, this greater efficacy was not found in the treatment-naïve cohort where effect sizes were similar (0.9-1) (Newcorn et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…An excellent example of what is considered to be a structured psychoeducation program for mental health has been developed by Colom and Vieta [40]; this program has shown efficacy in reducing core symptoms and the frequency of relapse while improving treatment adherence. Although no meta-analysis regarding the efficacy of these interventions in ADHD has been carried out [41] (the literature regarding this specific topic is particularly scarce in ADHD), some studies have demonstrated the potential of these programs to reduce symptoms, improve quality of life and improve parents' knowledge and treatment adherence [8,9,[41][42][43]. These types of interventions are probably underutilized in ADHD and in psychiatry generally.…”
Section: Encouraging Adherence To Treatments: the Role Of Educationmentioning
confidence: 99%